Involvement and Detachment: The Application of Figurational Sociology Methodologies in Consumer Research and Macromarketing. (March 2016) - Sinclair, Gary
The macro-micro dichotomy prevalent in consumer research has led to methodological issues this article explores. Drawing from figurational theory and using a three-year participant-observation of heavy metal fans as a case study, this article puts forward a potential route for synthesis between dominant micro and macro perspectives. Merging contemporary consumer research methods with broader figurational theories of historical change and figurational methods allows for a more holistic understanding of consumer communities. The methodological approach used elucidates the problematic aspects of studying contexts seen as controversial and, hence, emotionally charged and value-laden. Despite the shared importance that figurationalists and macromarketers hold for developing accounts that recognize the relationship between broader structural processes, the emphasis figurationalists place on attaining a balance between involvement and detachment conflicts with the prominence that macromarketing scholars give to using their research to "serve" society. The implications of this difference are discussed.